First archaeological evidence for ginger consumption as a potential medicinal ingredient in a late medieval leprosarium at St Leonard, Peterborough, England - Elena Fiorin; Charlotte A. Roberts; Marica Baldoni; Erin Connelly; Christina Lee; Claudio Ottoni; Emanuela Cristiani (Scientific Reports, 2024)
Abstract Leprosy was one of the most outwardly visible diseases in the European Middle Ages, a period during which leprosaria were founded to provide space for the sick. The extant documentary evidence for leprosy hospitals, especially in relation to diet, therapeutic, and medical care, is limited. However, human dental calculus stands to be an important source of information as it provides insight into the substances people were exposed to and accumulated in their bodies during their lives. In the present study, microremains and DNA were analysed from the calculus of individuals buried in the late medieval cemetery of St Leonard, a leprosarium located in Peterborough, England. The results show the presence of ginger (Zingiber officinale), a culinary and medicinal ingredient, as well as evidence of consumption of cereals and legumes. This research suggests that affected individuals consumed ingredients mentioned in medieval medical textbooks that were used to treat regions of the body typically impacted by leprosy. To the authors' knowledge, this is the first study which has identified Zingiber officinale in human dental calculus in England or on the wider European continent.